Perfil epidemiológico da hanseníase em um município do interior do estado de Minas Gerais, Brasil (2001-2015) (Revista Brasileira de Pesquisa em Saúde/Brazilian Journal of Health Research, 2019)
Epidemiological profile of hansen’s disease in an inland county of Minas Gerais state, Brazil (2001-2015)